2015
DOI: 10.3109/11038128.2015.1049289
|View full text |Cite
|
Sign up to set email alerts
|

The power of power wheelchairs: Mobility choices of community-dwelling, older adults

Abstract: Background-Power wheelchairs are purported to have a positive effect on health, occupation, and quality of life. However, there is limited knowledge about what factors shape power wheelchair use decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Equipment use after stroke has been associated with personal factors (Scherer et al., 2011) and the timing of the introduction of equipment. For instance, three distinct stages of equipment use have been proposed in relation to the optimal timing of powered mobility aids: reluctant use, strategic use and essential use (Mortenson et al., 2015). It has also been suggested that the relationship between how someone with a disability views themselves and their abilities, as well as their equipment, impacts on equipment use (Lund and Nygard, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Equipment use after stroke has been associated with personal factors (Scherer et al., 2011) and the timing of the introduction of equipment. For instance, three distinct stages of equipment use have been proposed in relation to the optimal timing of powered mobility aids: reluctant use, strategic use and essential use (Mortenson et al., 2015). It has also been suggested that the relationship between how someone with a disability views themselves and their abilities, as well as their equipment, impacts on equipment use (Lund and Nygard, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These barriers include poorly maintained footpath infrastructure, difficult road crossings and the threat of embarrassment (Blaylock et al, 2015;Brouwer et al, 2008;Gallagher et al, 2011;McGrath et al, 2017;Montarzino et al, 2007). The need to improve community mobility conditions seems obvious, and is also supported by a range of other studies into the experiences of pedestrians with visual impairment, powered mobility device users and older pedestrians (Blaylock et al, 2015;Brouwer et al, 2008;Fomiatti et al, 2014;Gallagher et al, 2011;McGrath et al, 2017;May et al, 2010;Montarzino et al, 2007;Mortenson et al, 2015;Wilton and Davey, 2007).…”
Section: Key Resultsmentioning
confidence: 98%
“…They also suggest that occupational therapists have the necessary skills for comprehensive scooter assessment considering the range of suggested prerequisite skills (Townsend and Watson, 2013), and undoubtedly such a role is a natural progression from well-established roles in assessment of vehicle driving and wheelchair prescription. Occupational therapists are researching scooter use, as shown by studies from Australia (Maywald and Stanley, 2015), Canada (Mortenson et al., 2015) and the Netherlands (Cordes et al., 2018). As occupational therapists develop their role regarding scooters, evidence-based practice is essential to ensure decision-making is supported and consistent, especially for novice occupational therapists working in scooter prescription (Maywald and Stanley, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of wheelchair for users of a developed country might be inadequate in comparison to a developing country such as India because the users' needs are completely different. A number of studies have been performed to understand the technological needs and desires of users of wheelchair [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%